1971
DOI: 10.2136/sssaj1971.03615995003500060015x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of DDT on Solid Particles

Abstract: DDT adsorption from water by ion exchange resins, aluminum oxides, ion exchange celluloses, and soils was determined by measuring carbon‐14 labeled DDT remaining in solution. The positively charged adsorbents adsorbed more DDT from solution than the negatively charged adsorbents. In addition, the association of DDT with organic matter and colloidal clay in the aqueous phase resulting from sedimented soils increased DDT in solution.The chlorine atoms on the ethyl group of the DDT molecule possess a slight negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…It was also mentioned that the degree of retention among insecticides (DDT > methoxychlor > endosulfan) was inversely correlated with water solubility. Champion and Olsen (1971) suggested that DDT may be adsorbed to any positive charges on clays via the slight negative charges on the chlorine atoms of the ethyl group. Yaron et al (1967) studied aldrin adsorption by soils and clays and concluded that organic matter content and the ratio of clay to sand determined the amount of aldrin retained by the soil.…”
Section: Adsorption Of Chlorinated Hydrocarbon Insecticidesmentioning
confidence: 99%
“…It was also mentioned that the degree of retention among insecticides (DDT > methoxychlor > endosulfan) was inversely correlated with water solubility. Champion and Olsen (1971) suggested that DDT may be adsorbed to any positive charges on clays via the slight negative charges on the chlorine atoms of the ethyl group. Yaron et al (1967) studied aldrin adsorption by soils and clays and concluded that organic matter content and the ratio of clay to sand determined the amount of aldrin retained by the soil.…”
Section: Adsorption Of Chlorinated Hydrocarbon Insecticidesmentioning
confidence: 99%
“…Also, stainless steel was not a concern with respect to the organic volatiles Gillham and O'Hannesin 1990;Reynolds and Gillham 1986). Hydrophobic contaminants, including polyaromatic hydrocarbons, chlorinated pesticides, and polychlorinated biphenyls, will sorb onto impermeable materials (Champion and Olsen 1971;Ogan et al 1978;Jones and Miller 1988). However, because only a residual film remains on the impermeable surface of the stainless steel, aqueous solutes are quickly removed as new fluids pass over the surface, unlike certain polymers that allow the organics to be sorbed into the matrix.…”
Section: A151 Sorption Of Organic Contaminants Onto Materialsmentioning
confidence: 99%
“…The mechanism of p,p'-DDT adsorption to clays was thought to be an electrostatic attraction between aromatic hydrogen atoms of p,p'-DDT and negatively charged surfaces of the clays. Champion & Olsen (1971) have demonstrated the ability of a clay to remove 14 Cp,p'-DDT from water/dioxane (91:9, v/v) solution. They also showed that p,p'-DDT adsorption occurred to both positively and negatively charged adsorbents.…”
Section: Binding To Claysmentioning
confidence: 99%